Are eviscerations preventable? - JULIO FERNANDES TOMASI; FABIELLE MENEZES TOLFO; LAIS MADEIRA CONSTANTINO; FELIPE ANTÔNIO CACCIATORI (Revista do Colégio Brasileiro de Cirurgiões)
ABSTRACT Introduction: The incidence of eviscerations is 3.5% in the literature. The use of prophylactic meshes in patients at high risk of evisceration has been studied. The objective of this study is to evaluate the characteristics of patients undergoing abdominal wall resuturing due to evisceration and verify the benefit of using prophylactic mesh in this sample. Methods: This is a retrospective cohort study, which analyzed the medical records of patients who underwent abdominal wall resuturing procedures between January 2010 and December 2023 in a tertiary hospital. The inclusion criteria were patients who underwent abdominal wall resuturing in the study hospital, with index surgery in the same hospital and median access. Patients under 18 years of age, patients undergoing laparoscopic surgery and non-median access were excluded. The Rotterdam risk score for aponeurosis dehiscence, modified by Lima, was used as a parameter. Results: The final sample of 252 patients was made up of 74.2% men. The median age was 64 years and the median BMI was 24.3kg/m2. The median number of days between surgery and resuturing was 8. The median hemoglobin was 11.1g/dL. The incidence of neoplasia, smoking and COPD was 47.2%, 32.1% and 13% respectively. Elective surgeries were 58.8%. Conclusion: It was concluded that, using the modified Rotterdam score, of the 227 patients, 164 (72.2%) would have received prophylactic mesh, which potentially would have prevented evisceration.